2006
DOI: 10.1108/02635570610653498
|View full text |Cite
|
Sign up to set email alerts
|

Organizational factors to the effectiveness of implementing information security management

Abstract: Purpose - This paper aims to examine the influence of organization factors on the effectiveness of implementing BS7799, an information security management (ISM) standard. Design/methodology/approach - Based on literature review, a research model was formulated by extracting the antecedents of ISM, and an empirical study was conducted to show how the organizational factors influence organizations in carrying out BS7799. Findings - The study result revealed that there were significant impacts of organizational f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Management's IT competence and environmental uncertainty in industries positively influence organizational ISS management (Chang & Ho, 2006). Business managers with greater IT competence assume stronger ISS management leadership roles and demonstrate greater confidence in ISS management (Chang & Ho, 2006).…”
Section: Employee Compliance With Iss Policy and Controlsmentioning
confidence: 99%
See 4 more Smart Citations
“…Management's IT competence and environmental uncertainty in industries positively influence organizational ISS management (Chang & Ho, 2006). Business managers with greater IT competence assume stronger ISS management leadership roles and demonstrate greater confidence in ISS management (Chang & Ho, 2006).…”
Section: Employee Compliance With Iss Policy and Controlsmentioning
confidence: 99%
“…Environmental uncertainty increases competition within industries, driving IS innovation and increasing dependence on information systems (Chang & Ho, 2006;Kearns & Lederer, 2004). Hsu et al (2012) found different factors influenced adoption and assimilation of ISS management.…”
Section: Employee Compliance With Iss Policy and Controlsmentioning
confidence: 99%
See 3 more Smart Citations